The APETALA-2-like transcription factor OsAP2-39 controls key interactions between abscisic acid and gibberellin in rice. - Mahmoud W Yaish; Ashraf El-Kereamy; Tong Zhu; Perrin H Beatty; Allen G Good; Yong-Mei Bi; Steven J Rothstein (PLoS Genetics, 2010)
The interaction between phytohormones is an important mechanism which controls growth and developmental processes in plants. Deciphering these interactions is a crucial step in helping to develop crops with enhanced yield and resistance to environmental stresses. Controlling the expression level of OsAP2-39 which includes an APETALA 2 (AP2) domain leads to phenotypic changes in rice. Overexpression of OsAP2-39 leads to a reduction in yield by decreasing the biomass and the number of seeds in the transgenic rice lines. Global transcriptome analysis of the OsAP2-39 overexpression transgenic rice revealed the upregulation of a key abscisic acid (ABA) biosynthetic gene OsNCED-I which codes for 9-cis-epoxycarotenoid dioxygenase and leads to an increase in the endogenous ABA level. In addition to OsNCED-1, the gene expression analysis revealed the upregulation of a gene that codes for the Elongation of Upper most Internode (EUI) protein, an enzyme that catalyzes 16α, 17-epoxidation of non-13-hydroxylated GAs, which has been shown to deactivate gibberellins (GAs) in rice. The exogenous application of GA restores the wild-type phenotype in the transgenic line and ABA application induces the expression of EUI and suppresses the expression of OsAP2-39 in the wild-type line. These observations clarify the antagonistic relationship between ABA and GA and illustrate a mechanism that leads to homeostasis of these hormones. In vivo and in vitro analysis showed that the expression of both OsNCED-1 and EUI are directly controlled by OsAP2-39. Together, these results reveal a novel mechanism for the control of the ABA/GA balance in rice which is regulated by OsAP2-39 that in turn regulates plant growth and seed production.